The Low Temperature Specific Heat of Pr0.65Ca0.35MnO3 - Zhiyong Han; Zhenzhu Jing (Advances in Condensed Matter Physics)
The low temperature specific heat of polycrystalline perovskite-type Pr0.65Ca0.35MnO3 manganese oxide has been investigated experimentally. It is found that the low temperature electron specific heat in zero magnetic field is obviously larger than that of ordinary rare-earth manganites oxide. To get the contribution of phonon to the specific heat precisely, the lattice specific heat is calculated by Debye model fitting. Results confirm that the low temperature specific heat of Pr0.65Ca0.35MnO3 is related to the itinerant electrons in ferromagnetic clusters and the disorder in the sample.